Projeto de Educação Ambiental e Lazer (PEDAL): dialogando a partir do cicloturismo na escola - Gonçalves Júnior, Luiz; Carmo, Clayton da Silva; Corrêa, Denise Aparecida [UNESP]; Colloca, Edson Aparecido (My University, 2011)
The PEDAL had beginning with an interested group in accomplishing walks and bicycle trips looking for fruition of the disentailed leisure of the consumption. The objective of this report of experience is to present the cicloturismo as an alternative of fruition of the leisure that has been making possible debates and reflections that seek to the understanding of alunos/as of the basic education on the interface among the themes leisure, environmental education and quality of the life. In this report we considered intervention accomplished at a school of fundamental teaching in the city of Saint Carlos-SP. Starting from the results of the analysis of the registrations produced pelos/as alunos/as, we considered that the theme, of interest of the same ones, raised the construction of significant reflections, such as: the possibility of the use of the bicycle as means of transportation for the work or for the leisure; the need of public politics that promote and guarantee safety and respect to the cyclist.

O PEDAL teve início com um grupo interessado em realizar passeios e viagens de bicicleta buscando fruição do lazer desvinculado do consumo. O objetivo deste relato de experiência é apresentar o cicloturismo como uma alternativa de fruição do lazer que tem possibilitado debates e reflexões que visam à conscientização de alunos/as da educação básica sobre a interface entre os temas lazer, educação ambiental e qualidade da vida. Neste relato consideramos intervenção realizada em uma escola de ensino fundamental na cidade de São Carlos-SP. A partir dos resultados da análise dos registros produzidos pelos/as alunos/as, consideramos que o tema, de interesse dos mesmos, suscitou a construção de reflexões significativas, tais como: a possibilidade do uso da bicicleta como meio de transporte para o trabalho ou para o lazer; a necessidade de políticas públicas que promovam e garantam segurança e respeito ao ciclista.
Environmental education and leisure (treadle): dialogue from the bicycle tourism at school
Keywords: Quality of life; Leisure Activities; Environmental education; Qualidade de vida; Atividades de Lazer; Educação ambiental